2016
DOI: 10.3389/fpsyg.2015.02006
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience Function of Character Strengths in the Face of War and Protracted Conflict

Abstract: This study investigated the role of character strengths and virtues in moderating relations between conflict exposure and psychiatric symptoms among 1078 adolescents aged 13–15 living in southern Israel, who were exposed to lengthy periods of war, terrorism and political conflict. Adolescents were assessed for character strengths and virtues, political violence exposure using the Political Life Events (PLE) scale, and psychiatric symptoms using the Brief Symptom Inventory and the UCLA PTSD Index. Results confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 50 publications
6
42
1
2
Order By: Relevance
“…In line with previous reports on populations experiencing stress (e.g. Martínez-Martí & Ruch, 2017;Duan, 2016;Shoshani & Slone, 2016;Weber et al, 2013), we expect transcendence strengths (such as hope, gratitude, love, spirituality, and zest), and restraint strengths (including perseverance, prudence, and self-regulation) to be the most strongly associated with psychological distress and self-efficacy. It has repeatedly been suggested that these strengths are particularly important in giving individuals the energy and determination to face challenging situations and helping them to regulate their behavior under stressful circumstances.…”
Section: The Present Studysupporting
confidence: 88%
See 2 more Smart Citations
“…In line with previous reports on populations experiencing stress (e.g. Martínez-Martí & Ruch, 2017;Duan, 2016;Shoshani & Slone, 2016;Weber et al, 2013), we expect transcendence strengths (such as hope, gratitude, love, spirituality, and zest), and restraint strengths (including perseverance, prudence, and self-regulation) to be the most strongly associated with psychological distress and self-efficacy. It has repeatedly been suggested that these strengths are particularly important in giving individuals the energy and determination to face challenging situations and helping them to regulate their behavior under stressful circumstances.…”
Section: The Present Studysupporting
confidence: 88%
“…Following Niemiec's conceptualization (2019), these strengths may have both a reappraisal and a resilience function in a lockdown: they can support individuals' positive reframing of the situation, making them better able to appreciate smaller pleasures. Such a positive attitude is usually associated with better psychological outcomes, in both normal and exceptional conditions (Niemiec, 2013;Shoshani & Slone, 2016). As lockdown measures become less stringent, transcendence may also support people's resilience, possibly helping them to experience less psychological distress in the future as well (Martínez-Martí & Ruch, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study was conducted in Israel, a tumultuous political environment in which children are exposed to chronic political violence (Slone & Shoshani, 2014). This may impact different aspects of their meaning in life, SWB, and mental health (Shoshani & Slone, 2016;Slone & Shoshani, 2008). Hence the MIL-CQ should be utilized in different cultural contexts to draw broader conclusions regarding the development of meaning in life in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining the implications of this infiltration of political conflict into civilian life via the media has demonstrated its negative psychological impact, showing resultant increased anxiety (Slone, 2000; Slone and Shoshani, 2014a), anger (Yukawa et al, 2001; Slone et al, 2009; Slone and Shoshani, 2010), pity and fury (Sontag, 2005; Slone and Shoshani, 2006a, 2008b), risk behaviors (Shoshani et al, 2014, 2016), and symptoms of Post Traumatic Stress Disorder, such as nightmares, anxiety, and fear (Joshi and Kaschak, 1998; Slone et al, 2013; Shoshani and Slone, 2016). Studies of the effects of extended media exposure to the events of September 11th revealed associated high levels of post traumatic symptoms and an assortment of severe negative emotions from acute psychological distress to more prolonged feelings of vulnerability and insecurity (Gil-Rivas et al, 2004; Marshall and Galea, 2004).…”
Section: Diversity In Psychological Reactions To Media Coverage Of Wamentioning
confidence: 99%